2002
DOI: 10.1002/jmv.10168
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus transmission in Brazilian hemodialysis units: Serological and molecular follow‐up

Abstract: A serological and molecular study of hepatitis B virus (HBV) infection was carried out in dialysis units in Central Brazil. Between 1995 and 1999, serum samples from all HBsAg-positive hemodialysis patients (n = 43) were tested for HBeAg/anti-HBe and subtyping by monoclonal ELISA. HBV DNA was detected by PCR and positive samples were genotyped by restriction fragment polymorphism pattern (RFLP) methodology. TheHBsAg prevalence declined in this population during the survey period (12-5.8%). HBeAg and anti-HBe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
18
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
7
18
2
Order By: Relevance
“…One HBeAg/anti-HBe-negative patient also had HBV DNA detectable in his serum. These data were similar to those previously found by Teles et al (2002), which emphasize the need for rapid recognition and isolation of HBsAg-positive patients regardless of their HBeAg/anti-HBe status.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…One HBeAg/anti-HBe-negative patient also had HBV DNA detectable in his serum. These data were similar to those previously found by Teles et al (2002), which emphasize the need for rapid recognition and isolation of HBsAg-positive patients regardless of their HBeAg/anti-HBe status.…”
supporting
confidence: 91%
“…These genotypes have been found in other Brazilian hemodialysis populations (De Castro et al 2000, Teles et al 2002, Souza et al 2003 reflecting the HBV genotypes circulating in our country (Moraes et al 1996, Araujo et al 2004, Sitnik et al 2004. Genotype D was predominant in this hemodialysis patients (61.5%), as observed by others (De Castro et al 2000, Teles et al 2002). In addition, HBV isolates from genotype D have been involved in outbreak in dialysis units (De Castro et al 2000).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…However, this rate was lower than those observed in other studies conduced before the implementation of improved methods for prevention and control of infection in Brazilian hemodialysis units (Cenderoglo Neto et al 1995, Vanderborght et al 1995. In fact, recently Teles et al (2002) reported a decline of the HBsAg prevalence from 12%, in 1995, to 5.8%, in 1999, among hemodialysis patients from Goiânia city.…”
Section: Discussionmentioning
confidence: 73%
“…In developed countries where these measures have been implemented, HBV infection declined significantly, reaching hepatitis B surface antigen (HBsAg) rates lower than 1%, as observed in the US (Alter et al 1986, Tokars et al 2002. In Brazil, investigations have shown prevalence rates ranging from 4.4% to 15.1% (Cenderoglo Neto et al 1995, Busek et al 2002, Teles et al 2002.…”
mentioning
confidence: 99%